Environmental genotoxicity and cytotoxicity in the offshore zones of the Baltic and the North Seas - Rybakovas, Aleksandras; Barsiene, Janina; Lang, Thomas (Marine Environmental Research, 2009)
Micronuclei (MN), nuclear buds (NB) and fragmented-apoptotic cells (FA) were analyzed in mature peripheral blood and immature cephalic kidney erythrocytes of flounder (Platichthys flesus), dab (Limanda limanda) and cod (Gadus morhua) from 12 offshore sites in the Baltic Sea (479 specimens) and 11 sites in the North Sea (291 specimens), which were collected during three research vessel cruises in December 2002, 2003 and in September 2004. The highest levels of environmental genotoxicity (frequencies of MN up to 0.5‰, NB – up to 0.75‰) and cytotoxicity (FA – up to 0.53‰) were observed in flatfishes from areas close to oil and gas platforms in the North Sea and in zones related to the extensive shipping and potentially influenced by contamination from large European Rivers (Elbe, Vistula, Oder). In dab from the offshore zones of the North Sea, the levels of nuclear abnormalities were higher as compared to those in dab from the Baltic Sea. Responses in immature kidney erythrocytes were higher than in mature erythrocytes from peripheral blood. MN frequency lower than 0.05‰(the Baltic Sea) and lower than 0.1‰(the North Sea) could be suspected as a reference level in the peripheral blood erythrocytes of flatfish.